Fluid–structure modelling for material deformation during cavitation bubble collapse. (October 2021) - Sarkar, Prasanta; Ghigliotti, Giovanni; Franc, Jean-Pierre; Fivel, Marc
Abstract: The dynamics of cavitation bubbles and their interaction with solids has been studied for long, mostly on the macro-scale of sheet and vortex cavitation. Erosion takes place on small, concentrated areas of solid walls exposed to cavitation. One-way fluid structure interaction (FSI), in which the feedback of material deformation on the fluid is not considered, provides an adequate understanding of the underlying mechanism. However, in practical applications the solid material motion and deformation can significantly affect the bubble dynamics. This will, in principle, alter the structural loading, stresses and erosion in the solid. In this paper, we will report comparisons of one-way and two-way coupled FSI modelling using our finite volume based fluid solver YALES2 1 and finite element based solid solver Cast3M. 2 In two-way FSI coupling, the feedback of the solid wall deformation is considered in the fluid domain. To do so, we develop a compressible fluid solver with Arbitrary Lagrangian–Eulerian formulation to equip it with moving mesh capabilities in order to maintain a continuous fluid–solid domain. We present results using a step-wise coupling approach for two-way FSI and analyse the effects due to structural response on bubble dynamics and damping of impact pressures by different materials. Finally, we discuss our understanding on the need for one-way and two-way FSI modelling based on structural characteristics which can significantly affect the material erosion by nearby cavitation bubbles.